Pendidikan Agama Islam Berbasis Kearifan Lokal Lampung Menggala Tulang Bawang dalam Pelestarian Bahasa Indonesia - Palyanti, Mega; Ernawati; Safitri, Heriza Bela; Selvina, Selvina (CV. Creative Tugu Pena, 2024)
This research explores the role of local wisdom-based Islamic religious education in Lampung Menggala, Tulang Bawang, in preserving the Indonesian language. The integration between Islamic religious teachings and local wisdom of Lampung Menggala is considered important to ensure that religious values can be accepted and understood by the local community. Using a qualitative method, this study collected data through in-depth interviews, observations, and documentation studies. The results show that the use of Indonesian language in Islamic religious teaching, sermons, and Islamic literature facilitates a better understanding of religious values and local wisdom. Values such as Piil Pesenggiri, Juluk-adok, Nemui Nyimah, Nengah-Nyappur, and Sakai Sambaian, which are in line with Islamic teachings, can be conveyed effectively through Indonesian. In addition, this local wisdom-based religious education encourages young people to understand and appreciate their cultural heritage, thus helping to strengthen cultural identity and raising awareness of the importance of Indonesian as the unifying language of the nation. The study concludes with recommendations for further development in educational practices, including the integration of local wisdom into the Indonesian language, and the promotion of cultural heritage among young people.